Indium-mediated C-allylation of melibiose - Denner, Christian; Gintner, Manuel; Kählig, Hanspeter; Schmid, Walther (Beilstein Journal of Organic Chemistry, 2019)
The indium-mediated allylation reaction has been applied to melibiose, a disaccharidic substrate. This elongation methodology allows for a short, efficient and diastereoselective approach towards complex glycosylated carbohydrate structures. The stereochemical outcome of the key intermediates, allylated disaccharides, has been determined by X-ray analysis. Ozonolysis of the introduced double bond yielded the unprotected elongated disaccharides in the equilibrium of the pyranoid as well as furanoid isomers in both anomeric forms, respectively. Per-O-acetylation has been performed to facilitate separation of the isomeric mixture for structural identification. The main product revealed to adopt a β-pyranoid form of the elongated unit at the reducing end of the disaccharide.
Keywords: carbohydrates; C–C bond formation; indium-mediated allylation; melibiose; ozonolysis